A Review of "Optimal Fallow Period" Guidance Across Canadian Jurisdictions - Sonica Singhal; Julie Farmer; Anuj Aggarwal; JinHee Kim; Carlos Quiñonez (Elsevier, 2022)
Introduction: Understanding how different countries have responded to mitigate the risk of severe acute respiratory syndrome coronavirus 2 (SARS CoV-2) transmission in dental offices is important. This article describes the different approaches taken towards optimal fallow periods in Canadian jurisdictions. Methods: We searched publicly available information from dentist and dental hygiene regulator websites across the 10 provinces and 3 territories in Canada. We also searched for guidance documents on dental associations' websites or through personal communication with government officials. We extracted and tabulated information on fallow period recommendations or guidance, when available. Results: Nine jurisdictions (6 provinces and all 3 territories) acknowledge or provide guidance on fallow periods following aerosol-generating procedures. Among those who have provided guidance regarding a fallow period, recommendations follow the Centers for Disease Control and Prevention guidance if the air changes per hour (ACH) in the dental operatory is known. Conclusion: The evidence for deciding on optimal fallow period is limited and still being explored, resulting in substantial variation across Canadian jurisdictions. A focus on developing scientific evidence relevant to dentistry and assimilating existing science is crucial to establishing consistency and uniformity in information to deliver safe oral health care services.